Do Inflation, Labor, FDI, and External Debt Influence Economic Growth? Evidence from ASEAN Countries During the Fintech 3.0 - Aziz Zidan Maulana; Ida Ayu Putri Suprapti (Journal of Enterprise and Development (JED), 2025)
Purpose: This research aims to analyze the influence of inflation, labor, foreign direct investment (FDI), and external debt on economic growth in ASEAN countries during fintech 3.0 period.Method: This research employs a quantitative approach. The study includes 176 observations, comprising 11 cross-sectional units and 16 time series units. For data analysis, a panel data regression model is utilized, incorporating three approaches: the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Based on the results, the Fixed Effect Model (FEM) is identified as the best model. The data used in this study are secondary data obtained from international institutions such as the World Bank, Asian Development Bank (ADB), and International Monetary Fund (IMF).Result: The results indicate that inflation has a negative but insignificant effect on economic growth, while labor has a significant negative effect. In contrast, foreign direct investment (FDI) and external debt demonstrate significant positive effects, underscoring the importance of strategic management of these two variables to promote economic growth.Practical Implications for Economic Growth and Development: The research provides recommendations for consistently managing inflation, enhancing technology-based education and training for the workforce, and maximizing the benefits of FDI through strategic management. Additionally, the prudent use of external debt to finance productive sectors, particularly infrastructure, is crucial for promoting inclusive and sustainable economic development in the ASEAN region.